EDUKASI PENCEGAHAN HIV/AIDS MENGGUNAKAN MEDIA AUDIOVISUAL PADA SANTRIWAN DAN SANTRIWATI DIPONDOK PESANTREN ASSULAMY - Marthilda ida; Baiq Ruli Fatmawati; Melati Inayati Albayani; Kurniati Prihatin (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Indonesia has experienced a significant of HIV / AIDS cases. The youth group included that the vulnerable group to HIV / AIDS exposure. As an effort to prevent and transmit of HIV / AIDS, one of them was by conducting health education using audiovisual media, it is hope to increasing adolescent knowledge about HIV / AIDS prevention. This activity aims to provide information, knowledge and understanding of the dangers of free sex, STIs and HIV / AIDS and its transmission, this activity hope that in the future adolescents will better understand how HIV / AIDS transmitted, so number of people with HIV / AIDS can keep pressed. The method used was health education about the prevention of HIV / AIDS by involving students in Islamic boarding schools and evaluation using instruments. The result of community service activities is the enthusiastic response of students and in participating health education activities by being shown their presence and enthusiasm in participating in health education events. Based on the evaluation of the activity, there was an increase on knowledge about HIV / AIDS prevention using audiovisual media of all students. The conclusion in this activity is that health education was easy to accept and can increase knowledge about HIV / AIDS prevention using audiovisual media for students at Assulamy Islamic boarding school.